2017
DOI: 10.1016/j.celrep.2017.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Restricted Mammary Stem Cells Sustain the Development, Homeostasis, and Regeneration of the Estrogen Receptor Positive Lineage

Abstract: SummaryThe mammary gland (MG) is composed of different cell lineages, including the basal and the luminal cells (LCs) that are maintained by distinct stem cell (SC) populations. LCs can be subdivided into estrogen receptor (ER)+ and ER− cells. LCs act as the cancer cell of origin in different types of mammary tumors. It remains unclear whether the heterogeneity found in luminal-derived mammary tumors arises from a pre-existing heterogeneity within LCs. To investigate LC heterogeneity, we used lineage tracing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 37 publications
11
80
0
Order By: Relevance
“…Lineage-tracing of the luminal cell population has revealed that ER + progeny are restricted to the ER + lineage and, likewise, ER− progeny are restricted to the ER− lineage during pregnancy, lactation and involution 1517 . Furthermore, Wap-Cre, which is active only during pregnancy in the ER − alveolar cells, marked only ER − labeled cells after two pregnancies 18 .…”
Section: Mammary Epithelial Cells Have Limited Plasticity In Vivomentioning
confidence: 99%
“…Lineage-tracing of the luminal cell population has revealed that ER + progeny are restricted to the ER + lineage and, likewise, ER− progeny are restricted to the ER− lineage during pregnancy, lactation and involution 1517 . Furthermore, Wap-Cre, which is active only during pregnancy in the ER − alveolar cells, marked only ER − labeled cells after two pregnancies 18 .…”
Section: Mammary Epithelial Cells Have Limited Plasticity In Vivomentioning
confidence: 99%
“…The adult mammary epithelium consists of an arborized ductal network embedded within an adipose stroma (1). The ductal epithelium contains both luminal and basal cells, which are produced and maintained postnatally by lineage-restricted precursors (2)(3)(4)(5)(6)(7). During gestation, a coordinated program of epithelial proliferation, side-branching, differentiation and tissue remodeling takes place (1,8), resulting in the generation of thousands of alveolar structures that adorn the central ductal epithelium in lobular clusters (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recent lineage tracing studies from the Blanpain and Guo groups have identified potential ER-positive stem cells that can maintain the ER-positive lineage through multiple rounds of grafting! (Van Keymeulen et al, 2017;Wang et al, 2017). This ER-positive stem cell (marked "H" in Fig 1) is potentially the cell of origin of human luminal and molecular tumours.…”
Section: Introductionmentioning
confidence: 94%